Paul and the Apocalyptic Imagination - Blackwell, Ben C., 1974-; Maston, Jason, 1978-; Goodrich, John K (Book collections on Project MUSE., 2016)
Since the mid-twentieth century, apocalyptic thought has been championed as a central category for understanding the New Testament writings and the letters of Paul above all. But "apocalyptic" has meant different things to different scholars. Even the assertion of an "apocalyptic Paul" has been contested: does it mean the invasive power of God that breaks with the present age (Ernst Kásemann), or the broader scope of revealed heavenly mysteries, including the working out of a "many-staged plan of salvation" (N. T. Wright), or something else altogether? Paul and the Apocalyptic Imagination brings together eminent Pauline scholars from diverse perspectives, along with experts of Second Temple Judaism, Hellenistic philosophy, patristics, and modern theology, to explore the contours of the current debate. Contributors discuss the history of what apocalypticism, and an "apocalyptic Paul," have meant at different times and for different interpreters; examine different aspects of Paul's thought and practice to test the usefulness of the category; and show how different implicit understandings of apocalypticism shape different contemporary presentations of Paul's significance.